The Mediating Role of Empathy in the Internal Mechanism of Film-Induced Tourism - Yi, Kui; Li, Fengcai; Zeng, Yanqin; Xie, Changqing; Xu, Ziqi (Frontiers in Psychology, 2022)
With the advent of the information age and rapid advancement of digital technology, film and television tourism is developing swiftly under the joint forces of the film industry and tourism industry, emerging as a crucial form of cultural and entertainment consumption for individuals to pursue a better life in the new age. This study designs three experiments from the perspectives of identity conversion, motivation transfer and demand change to conduct an empirical study on the mediating role of empathy to explore the internal mechanism of film-induced tourism in the field of film and television tourism. The findings suggest that the three mediation hypotheses are all valid, indicating that the film-induced tourism involves identity conversion from audiences to visitors, motivation transfer from watching to travelling, and demand change from interest to expectation through emotional media.